PRIMARY STUDENTS’ MATHEMATICAL LITERACY: A CASE STUDY - Rooselyna Ekawati; Susanti Susanti; Jian-Cheng Chen (Jurnal Infinity, 2020)
This paper analyses Indonesian primary students’ Mathematical literacy in solving PISA like problems. The instruments were administered to 254 sixth graders from five different regions in Surabaya, Indonesia with various social background. There were three contents (quantity, Uncertainty and data, space and shape) and three level problems (High, Medium and Easy) used to develop Mathematics Literacy Test (MLT). Three students’ categories (Good, Middle and Low) were established by cluster analysis methodology. The most students’ challenge on MLT was space and shape as well as uncertainty and data’s content problem. The description of profile of primary students’ mathematical literacy related to MLT are worthy to suggest the design of learning lines for primary students to have more opportunity to learn and solve Mathematics literacy problem.